The analysis of cognition and affection style in Malay essay of secondary school students through hermeneutic pedagogy method - Nachiappan Suppiah, Vijain Kumar Nisha Nair, Mohd Zulkafaly Fatimah, Sharom Siti Shakina, Akorede Quadri Mojeed, Andi Harikrishnan, (N/A, 2014)
The analysis of cognition and affection style in Malay essay of secondary school students through hermeneutic pedagogy method by Nachiappan Suppiah, Vijain Kumar Nisha Nair, Mohd Zulkafaly Fatimah, Sharom Siti Shakina, Akorede Quadri Mojeed, Andi Harikrishnan,